Sex differences in bladder cancer: understanding biological and clinical implications - Prakash Chaudhary; Biplab Singha; Hany A. Abdel-Hafiz; Maria Velegraki; Debasish Sundi; Swati Satturwar; Anil V. Parwani; Sergei I. Grivennikov; Sungyong You; Helen S. Goodridge; Qin Ma; Yuzhou Chang; et al. (Biology of Sex Differences)
Abstract Bladder cancer (BC) remains a significant global health concern, with substantial sex and racial disparities in incidence, progression, and outcomes. BC is the sixth most common cancer among males and the seventeenth most common among females worldwide. Over 90% of BC cases are urothelial carcinoma (UC) with high degrees of pathological heterogeneity. Molecular subtyping of BC has also revealed distinct luminal, basal, and neuroendocrine subtypes, each with unique genetic and immune signatures. Emerging research uncovers the biasing effects of the sex hormones with androgens increasing BC risk through both tumor cell intrinsic and extrinsic mechanisms. The sex chromosomes, including both the X and Y chromosomes, also contribute to the sex differences in BC. The effect of sex chromosome is both independent from and synergistic with the effects of sex hormones. Loss of the Y chromosome is frequently observed in BC patients, while an extra copy of the X chromosome confers better protection against BC in females than in males. Advent of advanced technologies such as multiomics and artificial intelligence will likely further improve the understanding of sex differences in BC, which may ultimately lead to personalized preventative and treatment strategies depending on the biological sex of patients. This review delves into the impacts of biology of sex on BC, emphasizing the importance of further research into sex-specific biology to improve cancer prevention and care.